Conformational Dynamics‐Guided Loop Engineering of an Alcohol Dehydrogenase: Capture, Turnover and Enantioselective Transformation of Difficult‐to‐Reduce Ketones. Issue 13 (2nd May 2019) - Liu, Beibei; Qu, Ge; Li, Jun‐Kuan; Fan, Wenchao; Ma, Jun‐An; Xu, Yan; Nie, Yao; Sun, Zhoutong
Abstract: Directed evolution of enzymes for the asymmetric reduction of prochiral ketones to produce enantio‐pure secondary alcohols is particularly attractive in organic synthesis. Loops located at the active pocket of enzymes often participate in conformational changes required to fine‐tune residues for substrate binding and catalysis. It is therefore of great interest to control the substrate specificity and stereochemistry of enzymatic reactions by manipulating the conformational dynamics. Herein, a secondary alcohol dehydrogenase was chosen to enantioselectively catalyze the transformation of difficult‐to‐reduce bulky ketones, which are not accepted by the wildtype enzyme. Guided by previous work and particularly by structural analysis and molecular dynamics (MD) simulations, two key residues alanine 85 (A85) and isoleucine 86 (I86) situated at the binding pocket were thought to increase the fluctuation of a loop region, thereby yielding a larger volume of the binding pocket to accommodate bulky substrates. Subsequently, site‐directed saturation mutagenesis was performed at the two sites. The best mutant, where residue alanine 85 was mutated to glycine and isoleucine 86 to leucine (A85G/I86L), can efficiently reduce bulky ketones to the corresponding pharmaceutically interesting alcohols with high enantioselectivities (∼99% ee). Taken together, this study demonstrates that introducing appropriate mutations at key residues can induce a higher flexibility of the active site loop, resulting in the improvement of substrate specificity and enantioselectivity. Abstract :